The Right to Reasons for Administrative Action in Zimbabwe - Kasuso, Tapiwa Givemore; Manyatera, Gift (Unisa Press, 2022)
The so-called ‘third wave’ of democratisation in Africa has witnessed a transition from a culture of impunity in the exercise of public power to more emphasis on a culture based on legality and the protection of fundamental rights of citizens. Important strides have been made in enhancing accountability by those who wield public power through judicial review mechanisms. The right to reasons for any administrative action that has an impact on citizens becomes even more paramount in light of these shifts in democratic ethos. This article focuses on the right to reasons for adverse administrative action in Zimbabwe against the backdrop of the 2013 Constitution, which ushered in the dawn of a new era in so far as the scope of the right to just administrative action is concerned. A critical examination of the nature and scope of the right to reasons is undertaken. Insightful recommendations are then proffered to further enhance the practical meaning of the right in the context of the constitutionally entrenched right to just administrative action in Zimbabwe.